2016
DOI: 10.1007/s00167-016-4348-y
|View full text |Cite
|
Sign up to set email alerts
|

How does lower leg alignment differ between soccer players, other athletes, and non-athletic controls?

Abstract: Diagnostic study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 27 publications
3
37
0
3
Order By: Relevance
“…18 Within the literature there is some evidence suggesting that increased participation in high-impact sports during youth would be associated with increased varus alignment of the knee at the end of growth in males, mainly due to increased frequency of intense running and cutting maneuvers. 19 Furthermore, Norton et al have reported in a non-athletic population that a compensatory valgus of the hindfoot could be expected in the setting of a varus knee. 20 Whether the converse of this observation is true in professional players of high-impact sports with varus knees has yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…18 Within the literature there is some evidence suggesting that increased participation in high-impact sports during youth would be associated with increased varus alignment of the knee at the end of growth in males, mainly due to increased frequency of intense running and cutting maneuvers. 19 Furthermore, Norton et al have reported in a non-athletic population that a compensatory valgus of the hindfoot could be expected in the setting of a varus knee. 20 Whether the converse of this observation is true in professional players of high-impact sports with varus knees has yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Within the literature, there exists some evidence suggesting that increased participation in high-impact sports during youth is associated with increased varus alignment of the knee at the end of growth in male patients, mainly because of the increased frequency of intense running and cutting maneuvers. 8,34 In addition, Norton et al 25 reported in a nonathletic population that compensatory valgus of the hindfoot could be expected in the setting of a varus knee. Whether opposite findings would be true in professional players of high-impact sports with varus knees has yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Researches investigating sports participation and genu varum mostly focused on football and high correlation was determined between genu varum and football participation (Thijs, Bellemans, Rombaut, & Witvrouw, 2012). It is reported that frequency and degree of genu varum is higher in football players than sedentary (Colyn, Arnout, Verhaar, & Bellemans, 2016). Regular football training exposes the knee joint to load and torque pressures that contribute to genu varum in lower extremity.…”
Section: Introductionmentioning
confidence: 99%